Randomized comparison trial of density and context of upper limb intensive group versus individualized occupational therapy for children with unilateral cerebral palsy - Sakzewski, L.; Miller, L.; Ziviani, J.; Abbott, D.; Rose, S.; Macdonell, R.; Boyd, Roslyn (2015)
© 2015 Mac Keith Press. Aim: To determine whether short-term intensive group-based therapy combining modified constraint-induced movement therapy and bimanual therapy (hybrid-CIMT) is more effective than an equal total dose of distributed individualized occupational therapy (standard care) on upper limb motor and individualized outcomes. Method: Fifty-three children with unilateral cerebral palsy (69% males; mean age 7y 10mo, SD 2y 4mo; Manual Ability Classification System level I, n=24; level II, n=23) were randomly allocated, and 44 received either hybrid-CIMT (n=25) or standard care (n=19). Standard care comprised six weekly occupational therapy sessions and a 12-week home programme. Outcomes were assessed at baseline, 13 weeks, and 26 weeks after treatment. Results: Groups were equivalent at baseline. Standard care achieved greater gains on satisfaction with occupational performance after intervention (estimated mean difference -1.2, 95% CI -2.2 to -0.1; p=0.04) and Assisting Hand Assessment at 26 weeks (estimated mean difference 3.1, 95% CI 0.2-6.0; p=0.04). Both groups demonstrated significant improvements in dexterity of the impaired upper limb, and bimanual and occupational performance over time. The differences between groups were not clinically meaningful. Interpretation: There were no differences between the two models of therapy delivery. Group-based intensive camps may not be readily available; however, individualized standard care augmented with a home programme may offer an effective alternative but needs to be provided at a sufficient dose.